Mean platelet volume and neutrophil to lymphocyte ratio in patients with tinnitus: a case-control study - Yildiz,Selçuk (2022)
Abstract Introduction: Different theories have been proposed on the etiology of tinnitus, including metabolic and audiologic causes. We suggest that mean platelet volume and neutrophil to lymphocyte ratio levels change in tinnitus, indicating microcirculatory disturbance and inflammatory process in the etiopathogenesis of tinnitus. Objectives: We aimed to evaluate the mean platelet volume and neutrophil to lymphocyte ratio in patients with tinnitus in comparison to healthy controls. Methods: Retrospective case-control study. Two-hundred and eighty-seven patients aged 18-59 years and diagnosed with tinnitus in the Ear, Nose, and Throat Clinic between December 2014 and May 2017 (patient group) and 275 healthy individuals who applied for a hearing screening within the same time period (control group). Demographics, concomitant diseases, laboratory results, and audiometric data were recorded. Mean platelet volume and neutrophil to lymphocyte ratio were the outcome measures. Patients with hearing loss due to presbycusis or another reasons, and patients with anatomical disorders in the external and middle ear were excluded from the study by using physical examinations, pure audio audiometry results and radiological imaging. The upper age limit was set at 59 to exclude presbycusis patients. Results: The ratio of female patients was higher in patient group than control group (58.5%, n = 168 vs. 49.4%, n= 127; respectively; p = 0.033). The mean age of patient group was significantly higher than those of control group (44.89 ± 10.96 years and 38.37 ± 10.65 years, respectively; p = 0.001). The percentage of subjects with high mean platelet volume level was significantly higher in patient group than control group (9.4%, n = 27, and 3.1%, n = 8 respectively; p = 0.008). The mean neutrophil to lymphocyte ratio was higher in patients with tinnitus than control group (1.95 ± 1.02 and 1.67 ±0.57, p = 0.012). A neutrophil to lymphocyte ratio level of 2.17 and above is associated with 1.991 times higher risk of tinnitus (odds ratio = 1.99, 95% confidence interval 1.31-3.02). Conclusion: High mean platelet volume and neutrophil to lymphocyte ratio values are associated with idiopathic tinnitus, suggesting the role of vascular pathologies in etiology of tinnitus. Tinnitus may be a sign of underlying systemic or local disorders. Therefore, patients with tinnitus should undergo detailed evaluation including hematological indices.